Current developments for improving efficacy of allergy vaccines. (August 2015) - Sandrini, Alessandra; Rolland, Jennifer M; O'Hehir, Robyn E
<x xml:space="preserve">Abstract</x> Allergic diseases are prevalent worldwide. Allergen immunotherapy (AIT) is a current treatment for allergy, leading to modification of the natural course of disease. Mechanisms of efficacy include Treg through release of IL-10 and TGF-β and specific IgG4 blocking antibodies. Subcutaneous and sublingual routes are popular, but uptake is limited by inconvenience and safety concerns. Inclusion criteria limit application to a small proportion of allergic patients. New forms of immunotherapy are being investigated for more efficacious, convenient and safer options with promising advances in recent years. The rationale of reducing vaccine allergenicity to increase safety while improving immunogenicity led to investigation of T-cell epitope-based peptides and recombinant allergen derivatives. Additionally, different routes of administration and adjuvants and adjunct therapies are being explored. This review discusses the current status of AIT and recent advances to improve clinical efficacy, safety and long-term immune tolerance.